IMPLEMENTASI MEDIA PEMBELAJARAN BUSY BOOK UNTUK MENINGKATKAN KOGNITIF ANAK USIA DINI DALAM MENGENAL KONSEP BILANGAN DIKELOMPOK A RA INSAN MUBAROK - Ellyana Ilsan Eka Putri; Dayu Aliyatul Fikriyah; Riris Wahyuningsih (AL IHSAN: Jurnal Pendidikan Islam Anak Usia Dini, 2020)
Cognitive abilities are abilities that place more emphasis on human intellectual potential. Cognitive development of children aged 4-5 years in recognizing the concept of numbers, namely: 1) counting and calling the sequence 1-10. 2) counting 1-10 by showing the objects. 3) shows the sequence of numbers 1-10 with objects. 4) connect or pair the symbols of numbers 1-10 with objects. 5) denotes two sets which are equal, unequal, more, and less. Busy book learning media is a book made of cloth and contains simple game activities designed creatively as props. This study aims to improve children’s cognitive abilities in recognizing the concept of numbers in group A RA Insan Mubarok Tegalsari for the 2019-2020 academic year. This research is a qualitative descriptive study with research subjects, namely: A group of 13 children. Data collection techniques that researchers use are observation, interviews, and documentation. The result of research in improving cognitive abilities to recognize the concept of numbers through busy book learning media show that there is an increase in early childhood cognitive abilities in recognizing the concept of numbers in group A (ages 4-5 years) RA Insan Mubarok Tegalsari after learning to recognize the concept of numbers by implementing busy book learning media.